SYSTEM METHODS CONTROL RECONFIGURATION OF THE AIRCRAFT IN SPECIAL SITUATIONS IN FLIGHT - Шевчук, Дмитро Олегович; Кравчук, Микола Петрович; Вовк, Володимир Григорович; Ананьїна, Анна Вадимівна (Problems of Friction and Wear, 2019)
The article explains the possibility of applying the systemic methods of parametric, structural control and purpose reconfiguration. The article explains the possibility of applying the systemic of parametric methods, structural reconfiguration management and reconfiguration of the object control objectives to prevent the transition to the current flight situation into a catastrophic one and maintain the specified level of safety. The article presents a block diagram of a control system developed reconfigurable dynamic system, and describes how it works.